The Effect of Profitability Ratios and Capital Structure on Firm Value in Industrial Sector Manufacturing Companies Listed on the Indonesia Stock Exchange - Rosmegawati Rosmegawati; Sumihar M.L. Tobing; Suhikmat Suhikmat; Mohammad Jon Tasrif; Helmut Martahi Saoloan Tambunan (ITB AAS INDONESIA, 2023)
This study aims to analyze the effect of profitability and capital structure on the value of manufacturing companies in the pharmaceutical industry sector which are listed on the Indonesia Stock Exchange. Profitability in this study is measured using Return On Assets (ROA) and Return On Equity (ROE). The capital structure in this study is measured using the Debt To Equity Ratio (DER). This research approach uses a quantitative approach to determine the effect due to the variables studied and the data displayed in the form of numbers and analyzed using statistics. The samples in this study were 7 manufacturing companies in the pharmaceutical industry sector which were listed on the Indonesia Stock Exchange in 2016-2020. The data analysis technique used is multiple linear analysis. Partial test results show that measured profitability _ with Return On Assets (ROA) and Return On Equity (RO OE) has a significant effect on firm value Capital structure with DER has an effect on firm value. Profitability and capital structure simultaneously influence firm value. From the calculation of the coefficient of determination of 0.81_ or 81% of the company's value is influenced by profitability and capital structure. Keywords: ROA, ROE, DER, Tirm Value